Pembangunan Spot Foto sebagai Daya Tarik di Danau Kaolin Bangka Belitung - Herliansyah, Dwi; Siregar, Chandra A (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Kaolin Lake in Bangka Belitung, a former mining site, has transformed into a popular tourist destination due to its striking blue waters and white sandy mounds. The unique landscape offers strong visual appeal, particularly for younger generations seeking photogenic and shareable experiences on platforms like Instagram and TikTok. This study explores the development of photo spots as a key strategy to enhance the lake’s attractiveness and support sustainable tourism growth. The purpose of the research is to analyze how the creation of aesthetically designed photo spots contributes to visitor satisfaction, destination branding, and the local economy. A qualitative descriptive method was used, involving field observations, interviews with local stakeholders, and documentation analysis. The results show that the presence of thematic and creatively designed photo spots significantly increases visitor engagement and length of stay. Furthermore, these developments encourage local entrepreneurship and community participation. However, maintaining environmental sustainability and ensuring the authenticity of the natural landscape remain critical challenges. This study highlights the importance of integrating visual tourism trends with sustainable planning to develop competitive and responsible tourist attractions. The findings contribute to broader discussions on innovation in destination development, especially in post-mining areas.